ATTRIBUTION THEORY AND LEVEL OF INTERPRETATION IN RELATION TO ENVIRONMENTAL ISSUES (Gestão & Regionalidade, 2022)
The objective of this study was to verify the theories of attribution and the level of interpretation in relation to the environmental problem of garbage. Therefore, a theoretical reference was made on the evolution of the environmental discussion and the emergence of the concepts of sustainable development and sustainability, as well as the theories of attribution and the level of interpretation. The method was characterized by a quantitative approach, carried out through a series of nine surveys with 259 participants, investigating which agent to blame for the generation of garbage is attributed by the participants according to various manipulations in the information text. With that, it was clear the difficulty and resistance of the participants in taking the blame for the garbage and / or making this problem close, with the other agents being repeatedly blamed. This happened despite the gradually more incisive report in the course of the treatments used. As a consequence, a tendency towards distancing and abstraction is reflected in relation to environmental issues, which can contribute to a low engagement in later attitudes related to this.
Keywords: Environmental issue; sustainability; attribution theory; interpretation level theory.